Review: Study of Aflatoxin M1 Contamination Level in Raw Milk - Mohammedi, Zahra (Journal of Natural Sciences – Kabul University, 2020)
Microbial contamination is one of the causes of food spoilage in the world. Fungi are common contaminants of dairy products and are capable of spoiling these products, leading to off-odors, off-flavors, significant food waste, and economic losses. Aflatoxins are secondary metabolites produced by fungi, particularly Aspergillus flavus and Aspergillus parasiticus, and are known to be the most dangerous mycotoxins. Among the more than 20 types of aflatoxins identified, four types—AFB1, AFB2, AFG1, and AFG2—and two others, AFM1 and AFM2, have been identified as major contributors to pathogenicity in animals and livestock products. The carcinogenic role of these toxins is recognized, particularly with respect to their effect on liver tissue.